Brand Equity, Cultural Transformation and Changes in Shopping Behavior of Working Women in Bali - Karta, Ni Luh Putu Agustini; Widiastini, Ni Made Ary; Irwanti, Ni Ketut Dewi (Journal of Business on Hospitality and Tourism, 2023)
Brand equity is an important topic of discussion among working women as a form of self-existence. The purpose of this study was to analyze brand equity and cultural transformation influencing changes in shopping behavior of working women in Bali. A survey was conducted of 150 female workers in Bali regarding the context of understanding brand equity and their involvement in various cultural and religious activities in Bali. The findings of this study are: brand equity affects the consumptive behavior of working women in Bali. Cultural transformation in Bali influences the consumptive behavior of working women in Bali in complex ways. Brand perception as the only factor to be considered in shopping, or in cultural and religious activities in Bali; tends to give rise to new patterns of hedonistic behavior, which are not only among the class, but also among ordinary people. Overall, this study shows that brand equity and cultural transformation can influence the consumptive behavior of working women in Bali. This study can also be a reference for related parties to increase brand equity and cultural transformation influencing changes in shopping behavior of working women in Bali.